A new level of refinement at Sirah Heritage Holdings - Sahim, Ahmad Izzat Fauzan; Raja Yusof, Raja Nerina (Emerald Publishing, 2024)
Learning outcomes: At the end of the case study exercise, students will be able to evaluate a company’s competitive standing and formulate business growth strategies based on internal and external environment analysis, develop business strategies for a company to strategise product offerings and recommend promotional strategies for a company to best market new product offerings. Case overview/synopsis: This case study is about the Central Production Unit (CPU), a wholly owned subsidiary of Sirah Heritage Holdings Sdn. Bhd. (owner of the popular restaurant brand “Tuuu […] Dia Pak Tam”), which was initially set up to standardise production for the whole company. However, ever since the subsidiary was set up, the management realised a few pertinent issues that needed their attention. Firstly, the CPU was underutilised even with the large number of Tuuu […] Dia Pak Tam restaurants across Peninsular Malaysia. Furthermore, the CPU was also tasked to introduce new products and services that could attract consumers and increase the visibility of their restaurants, but the company had no idea how to promote its new products. This study aims to look at the issues faced by the CPU by applying analytical tools such as SWOT analysis, Ansoff matrix and promotion mix. Complexity academic level: This case study is designed for undergraduate and postgraduate students who are taking courses such as strategic management, marketing management and business development. This case study can also be used by training departments, corporate trainers and other relevant managers to improve growth strategies using business theories. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 8: Marketing